Does Ignoring Heterogeneity in Impacts Distort Project Appraisals? An Experiment for Irrigation in Vietnam - Van de Walle, Dominique; Gunewardena, Dileni (Washington, DC: World Bank, 2014)
Could the simplifying assumptions made in project appraisal be so far from the truth that the expected benefits of public investments are not realized? Using data for Vietnam, commonly used estimates of the benefits from irrigation investments based on means are compared with impacts assessed through an econometric modeling of marginal returns that allows for household and area heterogeneity using integrated household-level survey data. The simpler method performs well in estimating average benefits nationally but can be misleading for some regions, and, by ignoring heterogeneity, it overestimates gains to the poor and underestimates gains to the rich. At moderate to high cost levels, ignoring heterogeneity in impacts results in enough mistakes to eliminate the net benefits from public investment. When irrigating as little as 3 percent of Vietnam's non-irrigated land, the savings from the more data-intensive method are sufficient to cover the full cost of the extra data required, ignoring other benefits from that data.